2014
DOI: 10.1093/mnras/stu1287
|View full text |Cite
|
Sign up to set email alerts
|

3D radiative transfer in η Carinae: application of the SIMPLEX algorithm to 3D SPH simulations of binary colliding winds

Abstract: Eta Carinae is an ideal astrophysical laboratory for studying massive binary interactions and evolution, and stellar wind-wind collisions. Recent three-dimensional (3D) simulations set the stage for understanding the highly complex 3D flows in η Car. Observations of different broad high-and low-ionization forbidden emission lines provide an excellent tool to constrain the orientation of the system, the primary's mass-loss rate, and the ionizing flux of the hot secondary. In this work we present the first steps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
(120 reference statements)
2
26
0
Order By: Relevance
“…The overplotted orbit is also very misleading given the complexity of the η Car binary and does not take into account important photoionization effects due to the presence of the hot companion star (Clementel et al 2014(Clementel et al , 2015a, nor the presence of high velocity absorbing material in line-of-sight that is located within the WWC regions (Groh et al 2010;Madura et al 2013). As noted by Damineli et al (2008b), and supported by the work of Groh et al (2010) and Clementel et al (2015a,b), while some of the He I absorption in η Car may originate in the pre-shock wind of the primary star at velocities near the wind terminal speed of ∼ 420 km s −1 , a significant and likely dominant amount of absorption comes from dense post-shock wind material located in the WWC region.…”
Section: The He I Absorptions and Their Relation To The Central Binarymentioning
confidence: 99%
See 1 more Smart Citation
“…The overplotted orbit is also very misleading given the complexity of the η Car binary and does not take into account important photoionization effects due to the presence of the hot companion star (Clementel et al 2014(Clementel et al , 2015a, nor the presence of high velocity absorbing material in line-of-sight that is located within the WWC regions (Groh et al 2010;Madura et al 2013). As noted by Damineli et al (2008b), and supported by the work of Groh et al (2010) and Clementel et al (2015a,b), while some of the He I absorption in η Car may originate in the pre-shock wind of the primary star at velocities near the wind terminal speed of ∼ 420 km s −1 , a significant and likely dominant amount of absorption comes from dense post-shock wind material located in the WWC region.…”
Section: The He I Absorptions and Their Relation To The Central Binarymentioning
confidence: 99%
“…Three-dimensional (3D) hydrodynamical and radiative transfer simulations of η Car's binary colliding winds have provided crucial insights on the time-dependent geometry and ionization state of the WWCs, helping constrain the binary orientation, wind parameters, and locations where various observed emission and absorption features arise (Okazaki et al 2008;Parkin et al 2009Parkin et al , 2011Groh et al 2012a,b;Madura et al , 2013Madura et al , 2015Clementel et al 2014Clementel et al , 2015a. Using a 3D dynamical model of the broad, extended [Fe III] emission observed in η Car by the HST/STIS (Gull et al 2009), confirmed the orbital inclination and argument of periapsis derived by Okazaki et al (2008) and Parkin et al (2009) using X-ray data.…”
Section: Introductionmentioning
confidence: 99%
“…Our current models do not include an ionizing source at the location of η A . The reasons for this, discussed in Clementel et al (2014a), are related to the complexities of proper spectroscopic modeling of the dense, extended wind photosphere of η A , which requires inclusion of the many ionization states of metals up to and including iron. However, we note that during periastron passage, η B and the WWIR penetrate deep within the extended wind of η A , down into its hotter regions where He is ionized to He + .…”
Section: Discussionmentioning
confidence: 99%
“…As in previous works, we use the simplex algorithm (Ritzerveld & Icke 2006;Ritzerveld 2007;Paardekooper, Kruip & Icke 2010;Kruip et al 2010;Kruip 2011) to post-process 3D SPH simulation output (M13). For further details, we refer the reader to Clementel et al (2014a), C14b, and references therein. We also retain the naming convention used in M13, Clementel et al (2014a), and C14b when referring to the SPH and simplex simulations in this paper, namely, Case A (Ṁ η A = 8.5 × 10 −4 M ⊙ yr −1 ), Case B (Ṁ η A = 4.8 × 10 −4 M ⊙ yr −1 ), and Case C (Ṁ η A = 2.4 × 10 −4 M ⊙ yr −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation